EFFECT OF AJWA DATE SEED ON LIPID PROFILE OF DIET INDUCED HYPERLIPIDEMIC RABBITS - Zobia Mushtaq; Samina Kausar; Naheeda Kousar; Sadia Chiragh (Khyber Medical University Journal, 2017)
OBJECTIVE:  To evaluate the antihyperlipedemic effect of Ajwa date (Phoenix dactylifera) seed on serum lipid levels of diet induced hyperlipidemic rabbits.